2016
DOI: 10.1111/ggi.12766
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of chair stand time as a surrogate of gait speed in diagnosing sarcopenia

Abstract: Chair stand time might be useful as a surrogate of gait speed when screening for sarcopenia. Geriatr Gerontol Int 2017; 17: 659-661.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 6 publications
(8 reference statements)
0
21
0
Order By: Relevance
“…When it is not feasible to measure the usual gait speed, we recommend the 5CST as a surrogate measure of gait speed in community-dwelling older adults [ 93 ]. Based on the study by Nishimura et al, a gait speed of 1.0 m/s correlates with a cut-off of ≥12 s for 5CST [ 93 ]; this is also recommended by AWGS 2019 [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…When it is not feasible to measure the usual gait speed, we recommend the 5CST as a surrogate measure of gait speed in community-dwelling older adults [ 93 ]. Based on the study by Nishimura et al, a gait speed of 1.0 m/s correlates with a cut-off of ≥12 s for 5CST [ 93 ]; this is also recommended by AWGS 2019 [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that tandem balance test, gait speed, CST and HGS are valid and reliable measures to assess physical performance ( 22 , 23 ). Moreover, gait speed, CST and HGS have proven to be associated with sarcopenia according to the EWGSOP definition in community dwelling older adults ( 20 , 24 , 25 ). Unfortunately, the results of this study in geriatric outpatients did not show a single suitable physical performance measure to identify older individuals with sarcopenia.…”
Section: Discussionmentioning
confidence: 99%
“…AUC was defined as low <0.70, acceptable 0.70–0.80, excellent 0.80–0.90 and outstanding >0.90. To test diagnostic accuracy, CST and HGS were dichotomized: CST ≥13 seconds ( 14 , 20 ), and HGS <20 kilograms for females and <30 kilograms for males were considered low ( 21 ). Statistical analyses were performed using Statistical Package for Social Sciences (SPSS Inc, Chicago, USA), version 22.…”
Section: Methodsmentioning
confidence: 99%
“…It is also clinically plausible that higher grip strength (as a marker of upper limb strength) and shorter chair stands time (more representative of lower limb strength) were common determinants of all three performance metrics. Indeed, sarcopenia (low muscle mass and/or strength), of which both grip strength and the five chair stands test are indicative measures (50), has been associated with reduced gait speed and poor functional outcomes in older people (51)(52)(53). In our models, slower chair stands time was associated with a decline in UGS, MGS, and GSR once time increased beyond 14.2 s, 13 s, and 10.6 s, respectively; whilst increases in UGS, MGS, and GSR began at values of 13.4 s, 13 s, and 10.6 s, respectively.…”
Section: Common Featuresmentioning
confidence: 99%